Nosocomial Bacteremia Due to an As Yet Unclassified Acinetobacter Genomic Species 17-Like Strain - Rodriguez-Baño, Jesús (American Society for Microbiology, 2006)
We describe a case of bacteremia due to an as yet unclassified Acinetobacter genomic species 17-like strain. The recognition of this microorganism as non-Acinetobacter baumannii may have important epidemiological implications, as it relieves the hospital of the implementation of barrier precautions for patients infected or colonized as may be necessary with a multiresistant A. baumannii epidemic.